Advances in global leadership. Vol. 14 - Osland, Joyce S.; Reiche, B. Sebastian; Szkudlarek, Betina; Mendenhall, Mark E. (Advances in global leadership ;, 2022)
Advances in Global Leadership collects insights from leading scholars and practitioners and fresh ideas from promising newcomers to the field. As in Volume 13, we begin by focusing on global leadership in relation to the Covid-19 pandemic. Volume 14 is introduced with a tour-de-force analysis by twenty authors on the cross-cultural differences reflected in nineteen national responses to the global crisis. The resulting overarching lessons offer useful guidance to leaders grappling with the pandemic and beyond. This volume is organized as follows: * Part 1 presents research papers, many of which advance the conceptualization and practice of global leadership effectiveness, the topic promoted in our Call for Papers. Other chapters report on novel research that opens up pathways for other global leadership scholars. * The Practitioner's Corner in Part 2 features interviews with practitioners and scholar-practitioners whose work illustrates global leadership effectiveness, by modeling its practice, development, and teaching. * Finally, the editors reflect upon the contributions made toward advancing our understanding of global leadership effectiveness and suggest future research directions. Given its focus on important and timely global leadership topics, this book is a must-read for both scholars from wide-ranging disciplines and practitioners with a diverse set of global leadership roles. The Advances in Global Leadership series, with its finger firmly on the pulse of this exciting field, is an essential collection of global leadership knowledge and novel research approaches.